2004
DOI: 10.1002/cne.20158
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular and subsynaptic localization of group I metabotropic glutamate receptors in the monkey subthalamic nucleus

Abstract: Both subtypes of group I metabotropic glutamate receptor, mGluR1 and mGluR5, are expressed postsynaptically in neurons of the subthalamic nucleus (STN), and their activation induces different physiological responses. To test whether these effects could be explained by a differential localization of the two group I mGluRs, we analyzed the subcellular and subsynaptic distribution of mGluR1a and mGluR5 in the monkey STN. Double-immunofluorescence and light microscopic analyses revealed that both group I mGluR sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 77 publications
3
67
0
Order By: Relevance
“…These studies showed that brain tissue from mGluR1a knockout mice did not display any specific mGluR1a labeling compared to wild-type. In addition, immunoblotting of cells transfected with mGluR1a, but not mGluR5, labeled a band of 140kD (Kuwajima et al, 2004). Preadsorption studies in rat retina cells abolished mGluR1a labeling (Koulen et al, 1997).…”
Section: Primary Antibodiesmentioning
confidence: 92%
See 1 more Smart Citation
“…These studies showed that brain tissue from mGluR1a knockout mice did not display any specific mGluR1a labeling compared to wild-type. In addition, immunoblotting of cells transfected with mGluR1a, but not mGluR5, labeled a band of 140kD (Kuwajima et al, 2004). Preadsorption studies in rat retina cells abolished mGluR1a labeling (Koulen et al, 1997).…”
Section: Primary Antibodiesmentioning
confidence: 92%
“…Specificity of the mGluR5 antibody has been shown in previous studies from our laboratory using knockout mice, transfected cells and homogenates of rat brain. These studies showed that brain tissue from mGluR5 knockout mice do not stain for mGluR5 and HEK-293 cells transfected with mGluR5 label a band of the correct molecular weight (Kuwajima et al, 2004). Furthermore, immunoblot analysis on proteins isolated from various brain regions labels a band that corresponds to the size of mGluR5 in regions known to express mGluR5 protein and mRNA (Mannaioni et al, 2001).…”
Section: Primary Antibodiesmentioning
confidence: 99%
“…To localize group I mGluRs, we used rabbit antimGluR1a (Millipore, Billerica, MA) and rabbit anti-mGluR5 (Millipore) polyclonal antibodies. The mGluR1a and mGluR5 antibodies have previously been tested for specificity with Western immunoblot using samples from transfected cells (Marino et al, 2001;Kuwajima et al, 2004) and knock-out mice brain tissue (Ferraguti et al, 1998), as well as immunohistochemistry performed with antibody preabsorption (Testa et al, 1998) or on knock-out brain tissues (Kuwajima et al, 2004). For the immunoperoxidase localization of Homer proteins, rabbit polyclonal antibodies against H1b/c (1:5000), H2 (1:5000), and H3 (1:5000) were used (Shiraishi et al, 2003(Shiraishi et al, , 2004.…”
Section: Methodsmentioning
confidence: 99%
“…Group I metabotropic glutamate receptors (mGluRs) are G qcoupled heptahelical receptors that are widely expressed postsynaptically in basal ganglia nuclei, including the GP (Hanson and Smith, 1999) and STN (Kuwajima et al, 2004). Although coupled to the same second messenger cascade, mGluR1 and mGluR5 can serve different physiologic functions even when they are coexpressed in the same basal ganglia neurons (Valenti et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Although group II mGluRs are also widely distributed throughout the basal ganglia circuitry, the modulation of these receptors does not offer significant benefit in animal models of PD Conn et al, 2005;Niswender and Conn, 2010). The mGluR5 is heavily distributed postsynaptically in key basal ganglia nuclei, including the striatum, the globus pallidus, and the STN (Hanson and Smith, 1999;Smith et al, 2000Smith et al, , 2001Hubert et al, 2001;Paquet and Smith, 2003;Kuwajima et al, 2004;Conn et al, 2005;Kuwajima et al, 2007;Poisik et al, 2007;Niswender and Conn, 2010). In each of these structures, the localization and physiological properties of this receptor have been carefully studied in rodents and nonhuman primates Awad et al, 2000;Marino et al, 2001;Poisik et al, 2003;Conn et al, 2005;Galvan et al, 2006).…”
Section: Non-dopaminergic Therapiesmentioning
confidence: 99%